Penentuan Rute Distribusi Pada Perusahaan Distributor Multi Product dengan Pendekatan Nearest Neighbor (Studi Kasus : PT. XYZ Depo Blitar) - Lestari, Febrian Puji; Khoiroh, Siti Muhimatul (Jurnal Serambi Engineering, 2025)
PT. XYZ Depo Blitar is a multi-product distribution company with 128 customer partners. The company's deliveries exceed the working hours limit set by the company. However, the company does not pay overtime to its logistics employees. Therefore, this research was conducted to calculate the shortest distance on each route in order to save delivery time and costs. The method used in this research is quantitative method and the type of research applied is descriptive quantitative. The stages of data processing and data analysis use the nearest neighbour method. This method applies iteration to the location point that is the centre with the partner location point. The iteration aims to obtain the minimum and optimum distance of each route. The use of this method is to determine the optimal distribution route, distance efficiency and operating cost. Based on the data processing and analysis, the optimal percentage of distance savings and distribution operating costs can be obtained, namely 63.84% and 30.99% (Monday delivery), 61.27% and 24.74% (Tuesday delivery), 65.5% and 30.86% (Wednesday delivery), 43.15% and 8.15% (Thursday delivery), 45.97% and 21.26% (Friday delivery) and 64.75% and 26.09% (Saturday delivery). The total operating cost for one week's delivery is Rp. 1,884,892.3 for the research route.